The Metacognitive Knowledge of Adolescent Students During the Information Search Process - Bowler, Leanne (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The study used naturalistic methods to investigate the metacognitive knowledge of 10 adolescents as they searched for, selected, evaluated, and used information for a school-based, inquiry project. The study identified thirteen attributes of metacognitive knowledge related to the information search process: Knowing your strengths and weaknesses, knowing that you don’t ... Cette étude a utilisé les méthodes naturalistes pour examiner les connaissances métacognitives de 10 adolescents lors des processus de recherche, sélection, évaluation et utilisation de l’information, dans le cadre d’un projet de recherche scolaire. L’étude a identifié treize attributs de connaissances métacognitives liés au processus de recherche d’information : connaître ses forces et ses faiblesses, savoir qu’on ne connaît pas …